1999
DOI: 10.1051/aas:1999130
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated polarimeter for the MuSiCoS échelle spectrograph

Abstract: Abstract. We present in this paper the technical characteristics of a new polarimetric unit dedicated to the MuSiCoSéchelle spectrograph. The first test runs indicate that our instrument is very good at measuring polarisation or depolarisation structures in line profiles. It is therefore one of the very few facilities worldwide for studying magnetic topologies of active and chemically peculiar stars through rotational modulation of linearly and circularly polarised Zeeman signatures in line profiles. It is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 7 publications
(9 reference statements)
1
108
0
1
Order By: Relevance
“…The instrument consists of a fiberfed cross dispersed echelle spectrograph with a dedicated polarimeter (Donati et al 1999) mounted at the Cassegrain focus. Stellar light is collected in a 2 arcsec entrance over a spectral range from 4500 to 6600 Å and with a resolution R = 35 000.…”
Section: Spectropolarimetric Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument consists of a fiberfed cross dispersed echelle spectrograph with a dedicated polarimeter (Donati et al 1999) mounted at the Cassegrain focus. Stellar light is collected in a 2 arcsec entrance over a spectral range from 4500 to 6600 Å and with a resolution R = 35 000.…”
Section: Spectropolarimetric Observationsmentioning
confidence: 99%
“…Because the instrumental accuracy in continuum polarization is about 1% and the expected stellar continuum polarization is of the same order, the results obtained in the continuum cannot be trusted (see Donati et al 1999). However, polarization across emission lines can be studied with respect to the surrounding continuum.…”
Section: Linear Polarizationmentioning
confidence: 99%
“…To check the consistency of methods between this paper and that of Uytterhoeven et al (2008), a selection of the data taken as part of the 2007 multi-site spectroscopic campaign was analysed in famias. These data were provided as line profiles (as discussed in Uytterhoeven et al, 2008) which were computed using a Least-Squares Deconvolution (lsd) method (Donati et al 1997(Donati et al , 1999. This method differs slightly to the δ-function cross-correlation method used for the more recent hercules data, but produces very similar line profiles.…”
Section: Observations and Data Treatmentmentioning
confidence: 99%
“…With such instruments, the spectral resolution can be increased sufficiently to undertake polarimetric studies across stellar line profiles. It has become apparent, however, that "fringes" tend to appear in the data -see, for example, Tinbergen (1994), Harries & Howarth (1996) and Donati et al (1999). From their analysis, Harries and Howarth concluded that the observed fringes were consistent with being of the Fabry-Pérot-type producing a fringe-structured instrumental polarization which could be subtracted out by reference observations of unpolarized standard stars.…”
Section: Introductionmentioning
confidence: 99%